Effect of Transcutaneous Electrical Acupoint Stimulation on BUN, Serum T and Serum CK-MM Concentrations in College Athletes with High-level Football Match - Shoujiang LI; Jiapeng LI; Xiangjia KONG; Yong HU; Shijing YOU (康复学报)
Objective:To observe the impact of the transcutaneous electrical acupoint stimulation (TEAS) on blood urea nitrogen (BUN),serum testosterone (T) and serum creatine kinase isoenzyme-MM (CK-MM) of college athletes in high-level football match.Methods:Twenty-four college football players were randomly divided into control group, Group 1 and Group 2,with eight athletes in each group. The athletes in Group 1 and Group 2 were interfered by TEAS during the training, before and after the match. In the meanwhile, BUN, T, and CK-MM concentrations were tested at different stages.Results:There was no statistically difference of BUN, T, and CK-MM during training (P>0.05).However, BUN and CK-MM concentrations of the athletes in Group 1 and Group 2 during the stages of assembling training, match, and recovery were lower than those of the control group (P<0.05 or P<0.01),along with delayed decrease of T concentration (P<0.05 or P<0.01).Conclusion:The TEAS interference can effectively relieve the exercise-induced fatigue result from the load training with adaptive enhancement. But it makes no effect on the long time light-load training and heavy-load training. The TEAS interference has a better recovery in training fatigue during the training stage and after the match.